Paradise Lost and Seventeenth-Century Pageantry - Holland, Vivienne Kathleen (My University, 1974)
Recent scholarship has added to our knowledge about the court masque, reinforcing its significance for the literature of the sixteenth and seventeenth centuries. Milton's Comus has profited from such re-assessment so that its high valuation as dramatic literature need no longer be regarded as incompatible with its success as a court masque. The new seriousness of approach to the court masque in general and Milton's Comus in particular provides the impetus for an examination of the rest of Milton's poetic output for the purpose of tracing there the influence of his experience with the complimentary court entertainment.
The court entertainment was encomiastic in intent, this encomium being patterned according to certain conventions. Paradise Lost, which praises God, uses a number of these conventions. Contrary to usual epic practice, Milton does not immortalize worldly conquests and compliment the statesmanship of his nation's leaders. Early notions of a British epic, to use the Arthurian or other indigenous material, were abandoned in favour of a work to celebrate the heavenly king and the spiritual kingdom. In the finished poem epic structures are interpreted in ways suggestive of the influence of court pageantry. Encomium of the heavenly king is expressed in the God-centred structure of Paradise Lost. The whole action of the poem focusses on the throne of the omniscient viewer. The angels sing and dance about this throne as the court danced before royalty in the court entertainment, and even creation is the setting for "a Race of Worshippers" (VII.630). A foil to the glory of Heaven, provided in the parodic activities of the fallen angels in Hell, suggests the conventions of the antimasque and the comedy of misrule. The victorious reign of Christ is celebrated, as many a pageant celebrated the reign of a seventeenth-century king, in a tournament. A mock battle in which no one is maimed, this culminates in the triumphal entry of Christ himself in a pageant chariot, symbolically banishing, rather than waging battle with, the forces of evil. In Satan's pilgrimage to earth even the traditional epic wanderings are transformed into an allegoric progress. The devices of the court entertainment inform the action of the poem, which is made up of processions, ceremonies and masques. The scenic spectacle, too, is influenced by the theatrical effects and iconography of royal pageantry.
One might expect Heaven and Hell to be presented in terms of allegoric theatre, but in Paradise Lost even the garden itself is a golden world which works according to the pastoral conventions that so often informed court entertainments. Adam and Eve are the poem's legendary rulers. As he describes the pomp of the prelapsarian kingdom, Milton relies on a knowledge of contemporary pageantry. Here such pageantry expresses the perfection of the most perfect earthly kingdom of all. Referring to a legend often used to glorify the British court, Milton says of Paradise: "Hesperian Fables true, / If true, here only" (IV.250-51). To see Paradise Lost in the context of the contemporary pageantry and masque theatre is to see it not as history reconstructed, but as historic incident transmuted through the use of a series of literary devices into encomiastic fiction. The fictional world of the poem is designed to justify the workings of God's creation; it glorifies the providence of the omnipotent creator.
Keywords: paradise, lost, pageantry, seventeenth-century, masque, pilgrimage